"Al-Fawāʾid al-ḍiyāʾiyya fī šarḥ al-Kāfiya" de Ǧāmī ou quand un poète se fait grammairien pour son fils - Larcher, Pierre (Arabica, 2017)
This note presents the commentary on Ibn al-Ḥāǧib’s (d. 646/1249) Kāfiya written by the Persian mystic poet Ǧāmī (d. 896/1492) for his son Ḍiyāʾ al-Dīn. It is mainly inspired by two other commentaries on the Kāfiya, Ibn al-Ḥāǧib’s own commentary and Raḍī l-Dīn al-Astarābāḏī’s (d. 688/1289) commentary, as well as it is inspired by the Ḥāšiya on this latter written by al-sayyid al-šarīf al-Ǧurǧānī (d. 816/1413). This note also provides information on new editions of these two commentaries.